Credit information sharing and firm innovation: Evidence from the establishment of public credit registries - Hou, Fangfang; Ng, Jeffrey; Xu, Xinpeng; Zhang, Janus Jian (Contemporary Accounting Research, 2025)
Abstract Lenders are reluctant to finance firms' innovation activities because such activities tend to be opaque, with a high likelihood of negative outcomes that could hamper loan repayment. We posit that public credit registries (PCRs), which play an important role in credit information sharing in many countries, can facilitate financing by reducing adverse selection and moral hazard and increasing bank competition. Using the staggered establishment of PCRs in different countries and an international firm–patent data set, we find that credit information sharing positively affects firm innovation, especially in firms that experience a larger increase in bank debt financing after the establishment of a PCR. This finding is consistent with the notion that credit information sharing promotes firm innovation by easing bank debt financing frictions. We also find a stronger effect in countries that experience a large increase in bank competition after the establishment of a PCR—consistent with increased bank competition serving as a channel through which credit information sharing facilitates bank debt financing, thereby generating a positive effect on firm innovation. The positive effect is more pronounced when the established PCR has features that promote credit information sharing. It is also more pronounced for opaque firms and firms in innovation‐intensive industries, indicating that credit information sharing helps to reduce financing frictions. Finally, we posit and find evidence that firm efficiency in transforming innovation inputs into outputs improves after the establishment of a PCR. Overall, our paper offers novel insights into how credit information sharing facilitates firm innovation.